External debt conversion schemes: analysis criteria - Shiguiyama, David; Vásquez, José Miguel (Universidad del Pacífico, 1989)
Right from the beginning of the External Debt crisis, a group of schemes emerged seeking to use the discounts with which the external debt papers are negotiated.From the debtor country standpoint, the application of these schemes offer both advantages and disadvantages, depending upon the country's economic conditions. Therefore, it is difficult to decide a priori whether the global balance is positive to the country's economy.However, such schemes may mean an important opportunity that debtor countries must tave advantage of this article is centered in the evaluation of two of the main debt conversion schemes, Le debt-for-equity (CDI) and debt-bonds swaps (CDB). Some analysis criteria are presented as a reference framework for the design and evaluation of such schemes.